1991
DOI: 10.1007/bf00002806
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sinks of dissolved organic carbon in a forested swamp catchment

Abstract: Abstract. Concentrations of dissolved organic carbon (DOC) were measured in precipitation, throughfall, stemflow, and soil, peat and stream water in a 50 ha catchment with a central 5 ha swamp at Mont St. Hilaire, Quebec. DOC concentrations in precipitation were low (2.0 mg L-l), but increased in passage through the tree canopies as throughfall (9.1-14.6 mg L-l) and stemflow (23.1-30.1 mg L-l). For the period July l-November 15, 1987, 0.5 g DOC m-* was imported as precipitation, and forest canopies contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
1
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(83 citation statements)
references
References 44 publications
(43 reference statements)
8
72
1
2
Order By: Relevance
“…The sorption affinity (m) and the soil carbon content are inversely related in some studies (Jardine and others Data compiled from Dalva and Moore 1991;Kaiser and others 1996;Moore and others 1992;Nodvin and others 1986;Qualls and Haines 1992;Vance and David 1992;Neff 1999. Kaiser and others 1996) and positively related in others (Moore and others 1992).…”
Section: Dissolved Organic Carbon In Terrestrial Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sorption affinity (m) and the soil carbon content are inversely related in some studies (Jardine and others Data compiled from Dalva and Moore 1991;Kaiser and others 1996;Moore and others 1992;Nodvin and others 1986;Qualls and Haines 1992;Vance and David 1992;Neff 1999. Kaiser and others 1996) and positively related in others (Moore and others 1992).…”
Section: Dissolved Organic Carbon In Terrestrial Ecosystemsmentioning
confidence: 99%
“…Fluxes of DOC generally decrease from the litter layer to deeper mineral hori-zons (Table 1). In virtually every soil with substantial clay content, DOC concentrations drop by 50%-90% from the surface organic layers to subsurface mineral soils (McDowell and Wood 1984;Cronan and Aiken 1985;Dalva and Moore 1991;Koprivnjak and Moore 1992;Dosskey and Bertsch 1997). Surface soil fluxes of DOC range from 10 to 85 g C m ÏȘ2 y ÏȘ1 ; below the surface horizons, they decline to 2-40 g C m ÏȘ2 y ÏȘ1 (Table 1).…”
Section: Model Generationmentioning
confidence: 99%
“…Different from CO 2 , DOC concentration from deeper depths was not stable under 8°C-AN condition. This was probably because soil DOC concentration is dependent on a balance between production from vegetation and SOM and consumption by soil organisms (Dalva and Moore, 1991;Jones et al, 2003;Van den Berg et al, 2012). The difference in organisms may lead to different consumption, and therefore instable DOC.…”
Section: Variations Among the Whole Depth Profilementioning
confidence: 99%
“…Foster and Grieve 1982;Cronan andAiken 1985: McDowell andLikens 1988;Moore 1989: Moore andDalva 1990). These studies have shown that organic matter concentrations in water increase as precipitation passes through the forest canopy, fore st floor, and organic soil horizon but decreases when passing through the mineraI soil horizon, remaining fairly constant thereafter as the water seeps into the streams.…”
Section: Sources Sines and Fluxes Of Docmentioning
confidence: 99%